Clinical results of the application of the transarticular fixation technique with the use of the device for the exact spokes conduction for fractures of the ankles with foot dislocation - Askar Serikbaev; Almas Dyusupov; Asanali Seitkabylov (National Scientific Medical Center, 2018)
Objective: To determine the comparative clinical outcomes and quality of life of patients with ankle fractures with dislocation of the foot using the transarticular fixation technique. Material and methods: 232 patients with closed fractures of the ankles, accompanied by subluxation or dislocation of the foot at the age of 19 to 75 years (mean age - 45.6 ± 2.4 years) were examined. The subjects were divided into 2 groups - the main group (142 patients - 61.2%) and comparisons (90 - 38.8%). In the treatment of patients of the main group, the method of transarticular fixation of the foot to the tibia was used, using a device specially developed for this purpose. The patients of the comparison group underwent an operation of open osteosynthesis with knife plates with screws or a wire loop. Comparison of clinical indices, functional outcomes and quality of life was performed using the FOAS technique. Results: The average for the main group of complications was 11.3%, for the comparison group - 35.6% (χ2 = 19.80, p = 0.002). The use of the technique of transarticular fixation contributed to a decrease in the treatment period by 8.6 days (p> 0.05). Excellent functional results were obtained in the main group by 25.4% more often, although the differences were insignificant. Unsatisfactory results were observed only in the comparison group. Significant differences in quality of life in favor of the main group were determined on the basis of the "pain" scale of the FOAS questionnaire at a 6-month follow-up period (46.7%, p<0.05). On the scale of "sports and recreation" similar differences were revealed in the period of 6 and 9 months. Conclusion: The use of the transarticular fixation method in our study turned out to be expedient and gave better results than open interventions with respect to the clinical course and the quality of life of patients.